As diretrizes curriculares nacionais para o ensino fundamental 1998 (DCNs/98) e o multiculturalismo como expressão do pensamento pósmoderno em educação - Sbardelotto, Vanice Schossler (2009)
This paper presents the results of a research which goal was understand the multifunctional character of National Curriculum Guides for Fundamental Teaching of 1998 DCNs/98. Those Guidelines are done by Câmara de Educação Básica do Conselho Nacional de Educação- a state organization- and its goal is define laws and principals and its purpose is to define laws and principals for the draw up of curriculums of public institutions that work with the fundamental teaching in Brazil.. The DCNs/98, which are educational policies, are part of a bigger group of social policies defined by the State, base don the contradictions of civil society. Therefore, they are the result of those contradictions. Moreover, to understand the nature and role of the State is compulsory to understand the goings of a social policy, once the State plays the central role in keeping the capitalist society. In this context of global capitalism, the State has its role defined by neoliberal policies came from countries of central capitalism. This new configuration of the State take it away of the productive sector just to regulate the economic relationships. Therefore, public expenses are also alternated with the social policies expenses; those are still functional to the State, once they help it to build the common sense around a certain kind of society. The State actions, like the social politics are influenced by the ideology that is built in the result of the rearticulating of capitalism, it s about post modern ideology. This ideology influences all the section of the social life, particularly in the educational field. The multiculturalism is one of the expressions of post modern ideology in education, which preach with regard the cultural diversity as a way to hold the society conflicts caused by the different cultures, as racial and cultural prejudices. The presence of multiculturalism in the DCNs/98 deals with the necessities of the State in the contemporary economic context, in a moderate form, it also deals with contradictory the social movements which fight for workers real gains. From the consulted references, it defends that the multiculturalism contribute with the conservation of the capitalism society, because it promotes the fragmentation of the work class. In this way, the presence of multiculturalism in the DCNs/98 marks its conservative character.